2011
DOI: 10.1007/s00542-011-1278-y
|View full text |Cite
|
Sign up to set email alerts
|

Low cost fabrication of microelectrodes on plastic substrate

Abstract: A low cost method of fabricating thick film microelectrodes on plastic substrate for producing integrated plastic biochips is introduced in this paper. Microelectrodes for pumping liquid in a PCR plastic biochip were successfully fabricated using a metal stamp and commercially available Au films. Testing results show that the microelectrode produced with the metal stamp is more reliable and can last longer than those fabricated with sputtering techniques. The fabrication method demonstrated in this paper provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Metal electrodes are most commonly fabricated on silicon or glass substrates although there are reports describing electrode fabrication on plastic substrates aiming at creating low-cost (Xu et al, 2011) and easy to integrate electrodes for microfluidic applications (Matteucci et al, 2016;Šnita et al, 2009). Patterning electrodes on plastic substrates can be achieved in a cost-efficient way by screen printing (Metters et al, 2011) or by using a stencil or shadow mask in combination with e-beam evaporation (Amato et al, 2015;Xu et al, 2011). However, it may be challenging to fabricate electrodes capable of providing a reproducible electrochemical signal as well as a stable metal (e.g.…”
Section: Electrochemical Characterization and Re-usability Of The On-mentioning
confidence: 99%
See 1 more Smart Citation
“…Metal electrodes are most commonly fabricated on silicon or glass substrates although there are reports describing electrode fabrication on plastic substrates aiming at creating low-cost (Xu et al, 2011) and easy to integrate electrodes for microfluidic applications (Matteucci et al, 2016;Šnita et al, 2009). Patterning electrodes on plastic substrates can be achieved in a cost-efficient way by screen printing (Metters et al, 2011) or by using a stencil or shadow mask in combination with e-beam evaporation (Amato et al, 2015;Xu et al, 2011). However, it may be challenging to fabricate electrodes capable of providing a reproducible electrochemical signal as well as a stable metal (e.g.…”
Section: Electrochemical Characterization and Re-usability Of The On-mentioning
confidence: 99%
“…Integration of electrochemical detection with microfluidic devices offers advantages, such as possibility to miniaturize both the transducer (electrode) and instrumentation as well as multiplexing and automation of measurements without losing the performance (Nyholm, 2005;Sassa et al, 2008;Xu et al, 2009). In addition, electrochemical detection is affected by neither sample turbidity nor optical path length, and it is possible to fabricate low-cost detection systems with minimal power demand (Felipe et al, 2014;Xu et al, 2011). However, direct detection of analytes in a complex sample matrix can be challenging when the potential interfering compounds and the possibility for surface fouling of the transducer are taken into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…For integration in the microfluidic device, electrodes can be fabricated on silicon, glass, plastic, , or paper using either complex and time-consuming lithographic approaches ,, or by faster and less expensive methods based on screen printing, , or e-beam evaporation using a stencil or mask. ,, The eight electrode array, fabricated by e-beam evaporation on PMMA support and integrated into the LoD device, showed a high degree of reproducibility, as indicated from the eight overlaying CVs in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The authors group had developed micro injection molding machine a few years ago. Xu et al (2006) and Xu et al (2011) investigated the process of solid pellet conveying and realized the fabrication of microfluidic channels in their self-developed micro injection molding machine, respectively. Xie et al (2010b) reported their research on the bondings of the microfluidic channels to form a plastic biochip.…”
Section: Introductionmentioning
confidence: 99%